Therapeutic footwear : a comprehensive guide - Tyrrell, Wendy; Carter, Gwenda; ScienceDirect eBooks (Edinburgh ; New York : Churchill Livingstone, 2009)
THERAPEUTIC FOOTWEAR: A COMPREHENSIVE GUIDE gives authoritative and wide-ranging information to health professionals concerned with the prescribing and fitting of surgical and corrective footwear. Wendy Tyrrell and Gwenda Carter have combined their many years of teaching and clinical experience to produce a textbook that is accessible, clear and without doubt the most definitive account of the subject currently available. Broad in scope, the text ranges through patient assessment, suitability of styles, retail and bespoke footwear, orthoses, measuring and fitting, all from the relatively simple to the most complex of cases. There is no other available single resource that offers such complete support and guidance to practitioners who wish to prescribe, fit and assess the effectiveness of therapeutic footwear.
It's not just "a pair of shoes" -- Patient concordance -- The last -- Footwear components and construction methods -- Retail footwear -- Shoes for special purposes -- Footwear and orthoses -- Prescription footwear -- Footwear sole and heel units -- Stock and modular footwear -- Measurements for bespoke footwear -- Fitting bespoke footwear -- Treating patients with complex pathologies -- Case studies.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Orthopedic shoes; Orthopedic shoes; Foot Diseases -- rehabilitation; Shoes; Foot Diseases -- physiopathology; Orthopedic Equipment; Electronic books